Media Use and Health Behavior in H1N1 Flu Crisis: The Mediating Role of Perceived Knowledge and Fear. - Zhang, Lingling; Kong, Ying; Chang, Hua (Atlantic Journal of Communication)
First detected in 2009, H1N1 flu has caused human causalities and become one of the top global health concerns. This study examined the relationship between the use of mass media for information about H1N1 flu and health-related behaviors. Past studies have focused primarily on the direct effects of media exposure on engagement in preventative behaviors. This study took a step forward by investigating the underlying mechanism in this relationship. Data from a web-based survey of college students showed that media use positively affected the likelihood of adopting preventative measures. Perceived knowledge and fear resulting from media exposure were important mediators of this process: Frequent exposure to media coverage of H1N1 flu led to higher levels of perceived knowledge and fear, which in turn translated into implementation of preventative measures.